ANALISIS KALIMAT PERINTAH (AMR) PADA SURAH YĀSĪN DALAM TERJEMAHAN AL-QUR’AN BACAAN MULIA HBJ - Maulana, Deni (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2019)
This study aims to find out how many forms of the command amr in surah YÄsÄ«n, and what translation techniques are used by HBJ. This research uses descriptive qualitative method with content analysis model. The source of the data in this study is the translation of the Al-Qur'an Bacaan Mulia by HBJ at surah YÄsÄ«n. Research shows that the form of amr amounts to 12 which means haqÄ«qi, researchers found seven verses. Spread on verses 11, 26, 45, 61, 64, 79, and 82. While from the form of amr means balÄgi means li-irsyÄd (suggestion) the researcher finds five verses. Spread on verses 13, 20, 21, 25, and 47. Furthermore, the translation technique used by HBJ in surah YÄsÄ«n, literal technique that dominates 80%. While the modulation technique is only 20%.